2018
DOI: 10.7717/peerj.5671
|View full text |Cite
|
Sign up to set email alerts
|

Growth and feeding of deep-sea coral Lophelia pertusa from the California margin under simulated ocean acidification conditions

Abstract: The global decrease in seawater pH known as ocean acidification has important ecological consequences and is an imminent threat for numerous marine organisms. Even though the deep sea is generally considered to be a stable environment, it can be dynamic and vulnerable to anthropogenic disturbances including increasing temperature, deoxygenation, ocean acidification and pollution. Lophelia pertusa is among the better-studied cold-water corals but was only recently documented along the US West Coast, growing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…In contrast, the direct link between POC flux and deep‐sea fish abundances has proven difficult to demonstrate (Bailey, Ruhl, & Smith, ), despite some evidence that increased surface production may fuel key fish prey taxa such as benthic invertebrates (Bailey et al, ; Drazen, Bailey, Ruhl, & Smith, ; Ruhl & Smith, ). Therefore, the projected decrease in food availability by 2100 in the North Atlantic (Gehlen et al, ; Gomez et al, ; Sweetman et al, ) may exacerbate the likely negative effects of other environmental changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the direct link between POC flux and deep‐sea fish abundances has proven difficult to demonstrate (Bailey, Ruhl, & Smith, ), despite some evidence that increased surface production may fuel key fish prey taxa such as benthic invertebrates (Bailey et al, ; Drazen, Bailey, Ruhl, & Smith, ; Ruhl & Smith, ). Therefore, the projected decrease in food availability by 2100 in the North Atlantic (Gehlen et al, ; Gomez et al, ; Sweetman et al, ) may exacerbate the likely negative effects of other environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple studies link reduced food availability to reduced physiological performance (e.g. calcification and respiratory metabolism) and condition of cold-water corals (Büscher et al, 2017;Larsson, Lundälv, & van Oevelen, 2013;Naumann, Orejas, Wild, & Ferrier-Pagès, 2011), as well as their ability to cope with ocean change (Büscher et al, 2017;Georgian et al, 2016;Gomez et al, 2019;Maier et al, 2016;Wood, Spicer, & Widdicombe, 2008). In contrast, the direct link between POC flux and deep-sea fish abundances has proven difficult to demonstrate (Bailey, Ruhl, & Smith, 2006), despite some evidence that increased surface production may fuel key fish prey taxa such as benthic invertebrates (Bailey et al, 2006;Drazen, Bailey, Ruhl, & Smith, 2012;Ruhl & Smith, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many studies showed no significant response in calcification rate under high pCO 2 (Maier et al, 2012(Maier et al, , 2013Form & Riebesell, 2012), but the conclusions were based on incubations shorter than in the present study. More recent literature shows, however, a decrease in net calcification of these species under acidified conditions (Maier et al, 2016;Gómez et al, 2018). The response of solitary species such as D. dianthus has been less explored, but some of the few experiments exhibited signs of physiological stress (Carreiro-Silva et al, 2014), especially at certain life stages (Movilla et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The response of solitary species such as D. dianthus has been less explored, but some of the few experiments exhibited signs of physiological stress (Carreiro-Silva et al, 2014), especially at certain life stages (Movilla et al, 2014). Regarding other stressors in addition to OA, few studies have been carried out with CWCs, but several examined their response to low pH and food availability (Maier et al, 2016;Georgian et al, 2016;Büscher, Form & Riebesell, 2017;Gómez et al, 2018). Being sessile suspension feeders, CWCs strongly depend on food resources from the water column, which are often scarce (Roberts, Wheeler & Freiwald, 2006), so food availability is very likely a key constraint that modulates the effects of environmental stressors such as OA in these species.…”
Section: Introductionmentioning
confidence: 99%